Makna Pelatihan Lintas Budaya bagi Expatriate: Sebuah Studi Fenomenologis di Asia Tenggara - Daniel Ananda Muhonis; Bryan Edward Tejo; Ari Anggarani Winadi Prasetyoning Tyas (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
In the era of globalization, multinational companies increasingly rely on expatriate assignments to support the success of international business operations. However, differences in values, norms, and cross-cultural communication patterns often pose significant challenges that affect expatriates’ adaptation processes and job performance in host countries, making cross-cultural training an important strategy in international human resource management. This study aims to gain an in-depth understanding of how expatriates interpret their experiences of participating in cross-cultural training and how such training influences their adaptation processes and performance in international business environments. This study employs a qualitative approach with a phenomenological study design. The research subjects are expatriates working in multinational companies in Southeast Asia, particularly in Indonesia, Malaysia, and Singapore, selected through purposive sampling. Data were collected through in-depth interviews and analyzed using thematic analysis to identify patterns of meaning related to cross-cultural training experiences, adaptation processes, cross-cultural communication challenges, and perceptions of job performance. The findings indicate that cross-cultural training is perceived as an essential process that helps expatriates understand local values and norms, enhance cultural sensitivity, improve cross-cultural communication skills, and strengthen self-confidence in carrying out professional tasks. These findings confirm the strategic importance of cross-cultural training in supporting successful expatriate adaptation and improved performance, and therefore highlight the need for its systematic integration into international human resource management policies.